P2X7 receptor contributes to long-term neuroinflammation and cognitive impairment in sepsis-surviving mice - Alves, Vinícius Santos; Silva, Joyce Pereira da; Rodrigues, Fabiana Cristina; Araújo, Suzana Maria Bernardino; Gouvêa, André Luiz; Leite-Aguiar, Raíssa; Santos, Stephanie Alexia Cristina Silva; Silva, Milla Souza Pessoa da; Ferreira, Fernanda Silva; Marques, Eduardo Peil; Passos, Beatriz Amanda Barbosa Rangel dos; Maron-Gutierrez, Tatiana; et al. (Frontiers in Pharmacology, 2023)
Sepsis is defined as a multifactorial debilitating condition with high risks of death. The intense inflammatory response causes deleterious effects on the brain, a condition called sepsis-associated encephalopathy. Neuroinflammation or pathogen recognition are able to stress cells, resulting in ATP (Adenosine Triphosphate) release and P2X7 receptor activation, which is abundantly expressed in the brain. The P2X7 receptor contributes to chronic neurodegenerative and neuroinflammatory diseases; however, its function in long-term neurological impairment caused by sepsis remains unclear. Therefore, we sought to evaluate the effects of P2X7 receptor activation in neuroinflammatory and behavioral changes in sepsis-surviving mice. Sepsis was induced in wild-type (WT), P2X7-/-, and BBG (Brilliant Blue G)-treated mice by cecal ligation and perforation (CLP). On the thirteenth day after the surgery, the cognitive function of mice was assessed using the novel recognition object and Water T-maze tests. Acetylcholinesterase (AChE) activity, microglial and astrocytic activation markers, and cytokine production were also evaluated. Initially, we observed that both WT and P2X7-/- sepsis-surviving mice showed memory impairment 13 days after surgery, once they did not differentiate between novel and familiar objects. Both groups of animals presented increased AChE activity in the hippocampus and cerebral cortex. However, the absence of P2X7 prevented partly this increase in the cerebral cortex. Likewise, P2X7 absence decreased ionized calcium-binding protein 1 (Iba-1) and glial fibrillary acidic protein (GFAP) upregulation in the cerebral cortex of sepsis-surviving animals. There was an increase in GFAP protein levels in the cerebral cortex but not in the hippocampus of both WT and P2X7-/- sepsis-surviving animals. Pharmacological inhibition or genetic deletion of P2X7 receptor attenuated the production of Interleukin-1β (IL-1β), Tumor necrosis factor-α (TNF-α), and Interleukin-10 (IL-10). Therefore, modulation of the P2X7 receptor in sepsis-surviving animals may reduce neuroinflammation and prevent cognitive impairment due to sepsis-associated encephalopathy, being considered an important therapeutic target.